Microstructure and Phase Composition of Yttria-Stabilized Zirconia Nanofibers Prepared by High-Temperature Calcination of Electrospun Zirconium Acetylacetonate/Yttrium Nitrate/Polyacrylonitrile Fibers - Vyacheslav V. Rodaev; Svetlana S. Razlivalova; Alexander I. Tyurin; Andrey O. Zhigachev; Yuri I. Golovin (Fibers, 2019)
For the first time, dense nanofibers of yttria-stabilized tetragonal zirconia with diameter of ca. 140 nm were prepared by calcination of electrospun zirconium acetylacetonate/yttrium nitrate/polyacrylonitrile fibers at 1100−1300 °C. Ceramic filaments were characterized by scanning electron microscopy, X-ray diffractometry, and nitrogen adsorption. With a rise in the calcination temperature from 1100 to 1300 °C, the fine-grain structure of the nanofibers transformed to coarse-grain ones with the grain size equal to the fiber diameter. It was revealed that fully tetragonal nanofibrous zirconia may be obtained at Y2O3 concentrations in the range of 2−3 mol% at all used calcination temperatures. The addition of 2−3 mol% yttria to zirconia inhibited ZrO2 grain growth, preventing nanofibers’ destruction at high calcination temperatures. Synthesized well-sintered, non-porous, yttria-stabilized tetragonal zirconia nanofibers can be considered as a promising material for composites’ reinforcement, including composites with ceramic matrix.